Experimental characterisation of dual-mass vibration energy harvesters employing velocity amplification. (December 2016) - Frizzell, Ronan; Kelly, Gerard; Cottone, Francesco; Boco, Elisabetta; Nico, Valeria; O'Donoghue, Declan; Punch, Jeff
Vibration energy harvesting extracts energy from the environment and can mitigate reliance on battery technology in wireless sensor networks. This article presents the nonlinear responses of two multi-mass vibration energy harvesters that employ a velocity amplification effect. This amplification is achieved by momentum transfer from larger to smaller masses following impact between masses. Two systems are presented that show the evolution of multi-mass vibration energy harvester designs: (1) a simplified prototype that effectively demonstrates the basic principles of the approach and (2) an enhanced design that achieves higher power densities and a wider frequency response. Various configurations are investigated to better understand the nonlinear dynamics and how best to realise future velocity-amplified vibration energy harvesters. The frequency responses of the multi-mass harvesters show that these devices have the potential to reduce risks associated with deploying vibration energy harvester devices in wireless sensor network applications; the wide frequency response reduces the need to re-tune the harvesters following frequency variations of the source vibrations.